Risk factors for delayed gastric emptying following laparoscopic repair of very large hiatus hernias. Issue 3 (28th August 2017) - Tog, C; Liu, D S; Lim, H K; Stiven, P; Thompson, S K; Watson, D I; Aly, A
Abstract: Background: Delayed gastric emptying can complicate surgery for hiatus hernia. The aim of this study was to quantify its incidence following laparoscopic repair of very large hiatus hernias, identify key risk factors for its occurrence and determine its impact on clinical outcomes. Methods: Data collected from a randomized trial of patients who underwent laparoscopic mesh versus sutured repair of very large hiatus hernias (more than 50 per cent of stomach in chest) were analysed retrospectively. Delayed gastric emptying was defined as endoscopic evidence of solid food in the stomach after fasting for 6 h at 6 months after surgery. Results: Delayed gastric emptying occurred in 19 of 102 patients (18·6 per cent). In univariable analysis, type 2 paraoesophageal hernia (relative risk (RR) 3·15, 95 per cent c.i. 1·41 to 7·06), concurrent anterior and posterior hiatal repair (RR 2·66, 1·14 to 6·18), hernia sac excision (RR 4·85, 1·65 to 14·24), 270°/360° fundoplication (RR 3·64, 1·72 to 7·68), division of short gastric vessels (RR 6·82, 2·12 to 21·90) and revisional surgery (RR 3·69, 1·73 to 7·87) correlated with delayed gastric emptying. In multivariable analysis, division of short gastric vessels (RR 6·27, 1·85 to 21·26) and revisional surgery (RR 6·19, 1·32 to 28·96) were independently associated with delayed gastric emptying. Delayed gastric emptying correlated with adverse gastrointestinal symptomatology, including higher rates of bloating, nausea, vomiting and anorexia, as well as reduced patient satisfaction with the operation and recovery. Conclusion: Delayed gastric emptying following large hiatus hernia repair is common and associated with adverse symptoms and reduced patient satisfaction. Division of short gastric vessels and revisional surgery were independently associated with its occurrence. Graphical Abstract: Delayed gastric emptying following hiatus hernia surgery is understudied. Here, we show that the incidence of delayed gastric emptying following large hiatus hernia repair is substantial and impairs patient outcomes. We have highlighted operative risk factors and potential areas for caution when performing laparoscopic hiatus hernia surgery to minimise the risk of this complication. More common after division of short gastric vessels and revision surgery